A study on the bankruptcy prediction using Altman model and Abbas & Rashid model / Salfarehan Suahnih - Suahnih, Salfarehan (2016)
This study aims to give the evidence of whether both Modal Altman and Abbas&Rashid Model have strong ability to predict bankruptcy among PN17 and Non Pn17 companies . Five variables are used of Altman Model which are the Working Capital over Total asset (WC/TA), Retained Earning over total asset(RE/TA), Earning before interest tax over total asset (EBIT/TA), Market value per Share over total asset (MVC/TA) and Sales to Total asset (SALES/TA). On the other Model, which is Abbas&Rashid Model, financial ratio used is Sales to total asset, cashflow and earning before interest tax to total liabilitis. This study covers the period of 2011 until 2015 using quarterly data of 6 listed companies in Bursa Malaysia Stock Exchange from PN17 and Non-PN17 companies. Results from the finding shows that Abbas&Rashi have strong ability to predict bankruptcy on Non-PN17 companies in Malaysia.